Preparation method of magnetic melamine hydrophobic oleophylic sponge

The magnetic melamine hydrophobic oleophobic sponge was prepared by extracting uruolol by impregnation method and ultrasonic method to cover magnetic nanoparticles, which solved the problems of low efficiency and environmental pollution in the prior art treatment of oil-containing wastewater, and achieved efficient and environmentally friendly oil adsorption effect.

CN119701894APending Publication Date: 2025-03-28陕西榆大科技发展有限公司

Patent Information

Application Number
CN202411908339.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to meet the needs of high efficiency and environmental protection when treating oil-containing wastewater. The preparation process of modified melamine sponges is complex and costly, and the chemical substances used are toxic, which affects the environment and the health of operators.

Method used

The melamine sponge was modified by the impregnation method, and the magnetic Fe3O4 nanoparticles were uniformly covered on the sponge by ultrasonic method, and the urolone was impregnated again to modify it to prepare a magnetic melamine hydrophobic lipophilic sponge.

Benefits of technology

It realizes the efficient oil adsorption capacity of the sponge, has good hydrophobicity and mechanical properties, is easy to recycling and recycling, and is simple in process, low in cost and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701894A_ABST
    Figure CN119701894A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a magnetic melamine hydrophobic oleophylic sponge, which comprises the following steps: extracting urushiol in raw lacquer by using acetone or ethanol as a solvent, and soaking a melamine sponge in a methanol solution of the urushiol to obtain a modified melamine sponge; the preparation method comprises the following steps: ultrasonically soaking the modified melamine sponge in a nano Fe3O4 dispersion liquid, and soaking the modified melamine sponge in a methanol solution of urushiol to obtain the magnetic melamine hydrophobic oleophylic sponge. After urushiol is extracted by taking a natural product raw lacquer as a raw material, the melamine sponge is modified, the surface energy of the sponge is reduced, and the hydrophobic effect of the sponge is enhanced, so that the selective adsorption capacity of the sponge to oil substances is enhanced, meanwhile, the mechanical property of the melamine sponge is improved, and the strength and toughness of the melamine sponge are improved; the modified sponge is not easy to damage in the adsorption process, and the service life is prolonged. The preparation method disclosed by the invention is simple to operate and low in cost, and the prepared magnetic hydrophobic oleophylic sponge has a remarkable application effect in the field of oil-water separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oily wastewater treatment, and in particular relates to a method for preparing a magnetic melamine hydrophobic and oleophilic sponge for treating oily wastewater. Background Art

[0002] As one of the byproducts of the petroleum industry, the wastewater generated during the processing, transportation and use of semi-coke contains a large amount of oil substances, which pose a serious threat to the environment. When oil substances are discharged into the natural environment, they will not only form a surface film, hinder oxygen exchange, and cause underwater organisms to suffocate due to lack of oxygen, but may also accumulate through the food chain and affect human health. In addition, oil substances will destroy the natural beauty of the water body and bring many inconveniences to the use of water resources.

[0003] There are many methods for industrial treatment of oily wastewater, including chemical, physical and biological methods. Chemical methods such as coagulation and oxidation can effectively separate and remove oil, but are often accompanied by the risk of secondary pollution; physical methods such as gravity separation, flotation and filtration are easy to operate, but the removal efficiency is not high; biological methods are environmentally friendly, but the treatment time and efficiency are easily affected by environmental factors. It can be seen that these methods have their own advantages and disadvantages, and it is difficult to meet the needs of high efficiency and environmental protection at the same time.

[0004] Melamine sponge has a wide range of applications in many fields due to its open-pore structure, high porosity, low density, high mechanical strength and low cost. Especially in the field of oil-water separation, melamine sponge has become an ideal adsorption material due to its unique physical and chemical properties. However, in order to meet the application requirements of extraction and enrichment of target substances in multi-lipid samples, it is necessary to modify the sponge surface, such as using a silane coupling agent to modify the melamine sponge. The invention patent with application number 201911201894.X discloses a method of modifying melamine sponge using a silane coupling agent and magnetic nano-iron tetroxide to obtain a magnetic melamine hydrophobic and oleophilic sponge. The specific steps are: immersing the melamine sponge in a toluene solution of a silane coupling agent with a mass fraction of 0.5% to 1%, and after complete immersion, the solvent is evaporated and dried, and ultrasonicated in an ethanol dispersion of nano-Fe3O4, and dried to obtain a magnetic melamine hydrophobic and oleophilic sponge. In this modification method, the solubility and reactivity of the silane coupling agent in toluene are limited, which affects the modification effect. In addition, the silane coupling agent requires specific conditions during the hydrolysis and condensation process, and self-condensation occurs during the hydrolysis process, thereby reducing the coupling performance and resulting in poor modification effect. Zhou Long et al. (Zhou Long, Du Guoyong, Deng Chunping. Preparation of superhydrophobic-superoleophilic melamine sponge and study on its oil-water separation performance [J]. China Plastics, 2023, 37(09): 28-38. DOI: 10.19491 / j.issn.1001-9278.2023.09.005.) prepared graphene oxide (GO) by an improved Hummers method. The reduced graphene oxide (rGO) obtained by high-temperature reduction of GO was first loaded on melamine sponge (MS) by a simple impregnation method, and then the MS was heated by diesel to load long-chain alkanes on the MS, successfully preparing a superhydrophobic-superoleophilic melamine sponge. The preparation process of this method is complicated, and the preparation and modification process of graphene oxide is costly, which increases the difficulty and cost of preparation and limits its popularity in industrial-scale applications. In addition, toxic or harmful chemicals such as hydrazine hydrate need to be used in the preparation process, which not only poses a threat to the health of operators, but may also cause pollution to the environment.Song et al. (Shuang Song, Hao Yang, Chunping Su, Zhibin Jiang, Zhong Lu, Ultrasonic-microwave assisted synthesis of stable reduced graphene oxide modified melamine foam with superhydrophobicity and high oil adsorption capacities [J] Chemical Engineering Journal, 2016, 306: 504-511.) prepared superhydrophobic reduced graphene oxide modified melamine foam by a simple ultrasonic-microwave synergistic method. This method also uses reduced graphene oxide modification, which is relatively costly, and tested several common oils (such as diesel, soybean oil, chloroform, etc.), but did not involve complex industrial oil mixtures or actual sewage containing suspended particles. Summary of the invention

[0005] The purpose of the present invention is to provide a new method for preparing a magnetic melamine hydrophobic and oleophilic sponge. The method has the advantages of simple process, safety, stability, low cost, long-lasting performance, and can significantly improve the adsorption capacity of oil substances. At the same time, magnetic materials are integrated to give it magnetic properties, thereby facilitating the recovery and recycling of the sponge.

[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention comprises the following steps:

[0007] Step 1: Use acetone or ethanol as solvent to extract urushiol from raw lacquer.

[0008] Step 2: Add the urushiol extracted in step 1 to methanol, stir and mix evenly to obtain a methanol solution of urushiol; completely immerse the melamine sponge in the methanol solution of urushiol, repeatedly squeeze and soak for 30 to 60 minutes, and then dry to obtain a modified melamine sponge with adhesion.

[0009] Step 3: Add nano-sized Fe3O4 to ethanol and disperse it evenly by ultrasonication to prepare a Fe3O4 dispersion; completely immerse the modified melamine sponge obtained in step 2 in the Fe3O4 dispersion, ultrasonicate for 10 to 30 minutes and then dry to obtain a magnetic melamine sponge.

[0010] Step 4: The sponge dried in step 3 is completely immersed in the methanol solution of urushiol again, squeezed and soaked repeatedly for 30 to 60 minutes and then dried to obtain a magnetic melamine hydrophobic and oleophilic sponge.

[0011] In the above step 1, the raw lacquer is added to acetone or ethanol, and stirred and evaporated at 40-60° C. for 40-48 hours to obtain lacquer phenol.

[0012] In the above step 1, preferably, the mass ratio of the raw lacquer to acetone or ethanol is 1:1.5-3.

[0013] In the above step 2, the mass fraction of urushiol in the methanol solution of urushiol is preferably 5% to 15%.

[0014] In the above step 3, the concentration of nano-Fe3O4 in the Fe3O4 dispersion is preferably 6 to 20 mg / mL.

[0015] The nano-sized Fe3O4 is Fe3O4 nanoparticles with a particle size of 100 to 250 nm.

[0016] Furthermore, in the above steps 2 and 4, the drying temperature is 70-80°C.

[0017] Furthermore, in the above step 3, the drying temperature is 50-60°C.

[0018] The beneficial effects of the present invention are as follows:

[0019] 1. The present invention adopts an impregnation method to prepare a melamine sponge modified with lacquer phenol, and then prepares a magnetic melamine sponge by an ultrasonic method, and finally impregnates the magnetic melamine hydrophobic and oleophilic sponge again, thereby making full use of the porous structure of the melamine sponge and ensuring the good performance of the adsorption material.

[0020] 2. The present invention uses raw lacquer as a raw material to extract lacquer phenol and then performs a modification treatment on the melamine sponge. Lacquer phenol has good adhesion and water resistance. The long side chain of hydrophobic nature can reduce the surface energy of the sponge and enhance its hydrophobic effect, thereby enhancing its adsorption capacity for oil substances; and lacquer phenol can improve the mechanical properties of the melamine sponge, increase its strength and toughness, and make the modified sponge less susceptible to damage during the adsorption process, thereby extending its service life; the surface of the melamine modified by lacquer phenol is rougher, which increases the contact area with oil substances, has a higher adsorption capacity, and exhibits selective adsorption of oil substances. In oily wastewater, it can preferentially adsorb oil substances, while less adsorption of water. This selective adsorption helps to reduce energy consumption and costs in subsequent treatment processes.

[0021] 3. The present invention uses ultrasonic technology to evenly cover the magnetic material on the sponge matrix. The cavitation effect caused by ultrasound can effectively prevent the aggregation of nanoparticles due to their small size and high surface energy, reduce the interaction between nanoparticles, and enhance the binding force between the particles and the sponge matrix. This magnetic melamine hydrophobic and oleophilic sponge is easy to recycle and reuse due to its magnetic properties. Even after multiple cycles, its oil adsorption performance remains stable and is almost unaffected.

[0022] 4. The preparation method of the present invention is simple and time-saving. The raw lacquer used is a natural product, non-toxic and harmless. The modified melamine sponge will not introduce new harmful substances when adsorbing oily wastewater, which is environmentally friendly. After the modified melamine sponge is saturated with adsorption, it can be recycled and reused through treatment, which helps to reduce the generation of waste and reduce environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a SEM comparison picture of the original melamine sponge (a), the magnetic melamine sponge obtained in Example 1 (b), and the magnetic melamine hydrophobic and oleophilic sponge (c and d) at different magnifications.

[0024] Figure 2 1 is a water contact angle diagram of the magnetic melamine hydrophobic and oleophilic sponge prepared in Example 1.

[0025] Figure 3 This is a test chart of the adsorption performance of the magnetic melamine hydrophobic and oleophilic sponge prepared in Example 1. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with embodiments and drawings, but the protection scope of the present invention is not limited to these embodiments.

[0027] Example 1

[0028] Step 1: Add 100 g of raw lacquer into 175 g of acetone, stir and evaporate at 50°C for 48 h to obtain lacquer phenol.

[0029] Step 2: Add 20 g of urushiol to 180 g of methanol, stir and mix for 1 hour to obtain a methanol solution of urushiol with a mass fraction of 10%; place a melamine sponge with a size of 2 cm×2 cm×2 cm at the bottom of a beaker, pour in a methanol solution of urushiol with a mass fraction of 10%, make the solution completely immerse the sponge, repeatedly squeeze and soak for 30 minutes, squeeze out the solution in the sponge, put the sponge in a fume hood, wait for the methanol to evaporate completely, and then put it in an oven at 75°C and dry it for 1.5 hours to obtain a modified melamine sponge with adhesion.

[0030] Step 3: Add 474 mg of magnetic Fe3O4 nanoparticles with a particle size of 200 nm into 30 mL of ethanol and disperse them evenly by ultrasonication to prepare a 16 mg / mL Fe3O4 dispersion; place the modified melamine sponge obtained in step 2 at the bottom of a beaker, pour in 16 mg / mL Fe3O4 dispersion to completely immerse the sponge, ultrasonicate for 10 minutes, take out and put it in an oven at 60°C to dry for 2 hours to obtain a magnetic melamine sponge.

[0031] Step 4: Place the sponge dried in step 3 at the bottom of a beaker, pour in a 10% methanol solution of urushiol by mass, make the solution completely immerse the sponge, squeeze and soak repeatedly for 30 minutes, squeeze out the solution in the sponge, place the sponge in a fume hood, wait for the methanol to evaporate completely, and then place it in an oven at 75°C and dry for 1.5 hours to obtain a magnetic melamine hydrophobic and oleophilic sponge.

[0032] Figure 1 a It can be seen that the surface of the unmodified original melamine sponge presents a three-dimensional network structure, which is relatively smooth and has abundant open pores; Figure 1 b It can be seen that after loading urushiol and magnetic Fe3O4, a coating is formed on the sponge surface and the roughness increases; and the magnetic melamine hydrophobic and oleophilic sponge obtained after urushiol modification again ( Figure 1 c and Figure 1 d) The skeleton is obviously covered with a large amount of particles, indicating that the sponge has been successfully coated with a layer of coating through urushiol modification.

[0033] The water contact angle test of the magnetic melamine hydrophobic and oleophilic sponge prepared in this example is as follows: Figure 2 As shown, its water contact angle is 140°, which shows that it has good hydrophobicity.

[0034] The adsorption performance of the magnetic melamine hydrophobic and oleophilic sponge prepared in this example was tested. The test results are as follows: Figure 3 As shown, after 20 consecutive adsorption tests, the adsorption effect of the sponge still remained above 93%.

[0035] Example 2

[0036] In step 2 and step 4 of this embodiment, the 10% by mass urushiol methanol solution in embodiment 1 is replaced by a 5% by mass urushiol methanol solution, and the other steps are the same as those in embodiment 1 to obtain a magnetic melamine hydrophobic and oleophilic sponge.

[0037] Example 3

[0038] In step 2 and step 4 of this embodiment, the 10% by mass urushiol methanol solution in embodiment 1 is replaced by a 15% by mass urushiol methanol solution, and the other steps are the same as those in embodiment 1 to obtain a magnetic melamine hydrophobic and oleophilic sponge.

[0039] Example 4

[0040] In step 3 of this embodiment, 300 mg of magnetic Fe3O4 nanoparticles with a particle size of 200 nm are added to 30 mL of ethanol, and ultrasonic dispersion is uniformly performed to prepare a 10 mg / mL Fe3O4 dispersion; the modified melamine sponge obtained in step 2 is placed at the bottom of a beaker, and the 10 mg / mL Fe3O4 dispersion is poured into the beaker so that the dispersion completely immerses the sponge, and after ultrasonication for 10 minutes, the sponge is taken out and placed in an oven at 60° C. for drying for 2 hours to obtain a magnetic melamine sponge. The other steps are the same as those in Example 1, and a magnetic melamine hydrophobic and oleophilic sponge is obtained.

[0041] Example 5

[0042] In step 3 of this embodiment, 200 mg of magnetic Fe3O4 nanoparticles with a particle size of 200 nm are added to 30 mL of ethanol, and ultrasonic dispersion is uniformly performed to prepare a 6.7 mg / mL Fe3O4 dispersion; the modified melamine sponge obtained in step 2 is placed at the bottom of a beaker, and the 6.7 mg / mL Fe3O4 dispersion is poured into the beaker so that the dispersion completely immerses the sponge, and after ultrasonication for 10 minutes, the sponge is taken out and placed in an oven at 60° C. for drying for 2 hours to obtain a magnetic melamine sponge. The other steps are the same as those in Example 1 to obtain a magnetic melamine hydrophobic and oleophilic sponge.

[0043] The oil adsorption performance of the magnetic melamine hydrophobic and oleophilic sponges prepared in the above Examples 1 to 5 and the magnetic melamine sponge prepared in step 3 of Example 1 (as comparative example 1) was tested. The specific process of the test was as follows: the magnetic melamine hydrophobic and oleophilic sponges were accurately weighed using an analytical balance, and the mass was recorded as m i ; Pour a sufficient amount of cooking oil into a beaker, add the pre-weighed magnetic melamine hydrophobic oleophilic sponge into it, ensure that the sponge adsorption capacity reaches saturation, weigh the sponge after adsorption, and record the mass as m t ; According to the formula: Q = (m t -m i ) / m i , calculate the oil absorption performance Q of the sponge, and the calculation results are shown in Table 1.

[0044] Table 1

[0045] sample Q(g / g) Example 1 97 Example 2 93 Example 3 89 Example 4 91 Example 5 93 Comparative Example 1 79

[0046] As can be seen from Table 1, in the magnetic melamine hydrophobic and oleophilic sponges prepared in Examples 1 to 5, when the mass fraction of the urushiol solution is 10% and the concentration of the magnetic Fe3O4 is 16 mg / mL, the obtained magnetic melamine hydrophobic and oleophilic sponges have the best performance and the best adsorption effect. The sponge obtained by soaking and modifying with urushiol and then impregnating Fe3O4 nanoparticles in Comparative Example 1 has significantly lower oil absorption performance than the sponge modified by soaking and modifying with urushiol again in Example 1.

Claims

1. A method for preparing a magnetic melamine hydrophobic and oleophilic sponge, characterized in that: The preparation method comprises the following steps: Step 1: Using acetone or ethanol as solvent, extracting urushiol from raw lacquer; Step 2: adding the urushiol extracted in step 1 to methanol, stirring and mixing evenly to obtain a methanol solution of urushiol; completely immersing the melamine sponge in the methanol solution of urushiol, repeatedly squeezing and soaking for 30 to 60 minutes, and then drying to obtain a modified melamine sponge with adhesion; Step 3: Add nano-sized Fe3O4 to ethanol and disperse it evenly by ultrasonication to prepare a Fe3O4 dispersion; completely immerse the modified melamine sponge obtained in step 2 in the Fe3O4 dispersion, perform ultrasonication for 10 to 30 minutes, and then dry to obtain a magnetic melamine sponge; Step 4: The sponge dried in step 3 is completely immersed in the methanol solution of urushiol again, squeezed and soaked repeatedly for 30 to 60 minutes and then dried to obtain a magnetic melamine hydrophobic and oleophilic sponge.

2. The method for preparing the magnetic melamine hydrophobic and oleophilic sponge according to claim 1, characterized in that: In step 1, the raw lacquer is added to acetone or ethanol, and stirred and evaporated at 40 to 60° C. for 40 to 48 hours to obtain lacquer phenol.

3. The method for preparing the magnetic melamine hydrophobic and oleophilic sponge according to claim 1 or 2, characterized in that: In step 1, the mass ratio of the raw lacquer to acetone or ethanol is 1:1.5-3.

4. The method for preparing the magnetic melamine hydrophobic and oleophilic sponge according to claim 1, characterized in that: In step 2, the mass fraction of urushiol in the urushiol methanol solution is 5% to 15%.

5. The method for preparing the magnetic melamine hydrophobic and oleophilic sponge according to claim 1, characterized in that: In step 3, the concentration of nano-Fe3O4 in the Fe3O4 dispersion is 6 to 20 mg / mL.

6. The method for preparing the magnetic melamine hydrophobic and oleophilic sponge according to claim 1 or 5, characterized in that: The nano-sized Fe3O4 is Fe3O4 nano-particles with a particle size of 100-250nm.

7. The method for preparing the magnetic melamine hydrophobic and oleophilic sponge according to claim 1, characterized in that: In step 2 and step 4, the drying temperature is 70-80°C.

8. The method for preparing the magnetic melamine hydrophobic and oleophilic sponge according to claim 1, characterized in that: In step 3, the drying temperature is 50-60°C.

Citation Information

Patent Citations

  • Preparation method of magnetic melamine hydrophobic oleophylic sponge

    CN111057267A

Cited By

  • Functionalized super-hydrophobic melamine sponge as well as preparation method and application thereof

    CN122124504A